Réponses

  • Utilisateur Brainly
2014-08-29T18:01:13+02:00
Résoudre les équations : 

x + 7 = - 2
x =  - 2 - 7
x = - 9

- x - 4 = 7
- 4 - 7 = x
- 11 = x

x/-3 = 72
x = 72 * (-3 )
x = - 216

2x + 1 = - 4
2x = - 4 - 1
2x = - 5
x = - 5/2

2(x - 3) = 11
2x - 6 = 11
2x = 11 + 6
2x = 17
x = 17/2
2014-08-29T18:27:55+02:00
Résoudre les équations :

1)
x + 7 = - 2
x = - 2 - 7
x = - 9

2)
- x - 4 = 7
- x = 7 + 4
x = - 11

3)
x /-3 = 72
x = 72 * - 3
x = - 216

4)
2x + 1 = - 4
2x = - 4 - 1
2x = - 5
x = - 5/2
x = - 2,5

5)
2 (x - 3) = 11
2x - 6 = 11
2x = 11 + 6
2x = 17
x = 17/2
x = 8,5